THE EFFECT OF TAX MINIMIZATION, BONUS MECHANISM, FOREIGN OWNERSHIP, EXCHANGE RATE, AUDIT QUALITY ON TRANSFER PRICING DECISIONS - Sanintya Mayantya; Priyono Puji Prasetyo; Marfuah Marfuah (Jurnal Bisnis Terapan, 2021)
Abstract The purpose of this study was to determine the effect of tax minimization, bonus mechanisms, foreign ownership, exchange rates, and audit quality on transfer pricing in manufacturing companies in Indonesia. The population of this research was all manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. By using the purposive sampling method, 81 companies were selected as the research sample. Based on logistic regression analysis, it was proven that the tax minimization variable has a significant positive effect on transfer pricing decisions. Likewise, the audit quality variable is proven to have a significant negative effect on transfer pricing decisions in manufacturing companies in Indonesia. Meanwhile, the bonus mechanism, foreign ownership, and exchange rate variables were not proven to have a significant effect on the company's transfer pricing decision. These results indicated that the greater the tax minimization carried out by the company and the lower the audit quality will increase the probability of the company in conducting transfer pricing, and vice versa. The results of this study have implications for encouraging the government to make regulations that can prevent transfer pricing practices between companies that have a special relationship that might harm the government from tax revenue. Keywords: bonus mechanism; foreign ownership; tax minimization; transfer pricing